Cellular protein HSC70 promotes fowl adenovirus serotype 4 replication in LMH cells via interacting with viral 100K protein - Shenyan Gao; Huayuan Chen; Xiaozhan Zhang; Jun Zhao; Zeng Wang (Poultry Science, 2022)
ABSTRACT: Fowl adenovirus serotype 4 (FAdV-4), the predominant causative agent of hepatitis-hydropericardium syndrome (HHS), has caused severe economic losses to poultry industry since 2015. Although fiber2 and hexon have been confirmed to be the virulence-related factors, the roles of nonstructural viral proteins in pathogenicity of FAdV-4 remain poorly understood. Here, a tandem mass spectrometry (MS) was used to identify host factors interacted with 100K protein of hypervirulent FAdV-4 isolate (CH/HNJZ/2015), and 2595 cellular proteins associated with many biological processes and pathways were identified according to Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses. Among the proteins, HSC70 was verified to interact with 100K through co-immunoprecipitation assay. Notably, overexpression of HSC70 promoted the replication of FAdV-4 in LMH cells, whereas blocking HSC70 with inhibitor ver-155008 markedly suppressed viral replication. Collectively, these findings suggested that many cellular proteins involved in FAdV-4 infection through interacting with 100K and HSC70 positively regulated virus replication.